Casebook of Orthopedic Rehabilitation Including Virtual Reality - Ip, David (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book is a companion text to Orthopedic Rehabilitation, Assessment, and Enablement by the same author, but can be used independently. Section 1 serves to illustrate through real-life examples the rehabilitation ideas and principles taught in the companion text, ranging from conditions seen daily by the orthopedic surgeon or primary care physician like knee and hip osteoarthritis or plantar fasciitis; through more challenging conditions like hamstring injury rehabilitation or heterotrophic ossification; to recent paradigm shifts in the management of osteoporosis and new technologies like vertebral fracture assessment using state-of-the-art DXA machines, hypergravity stimulation therapy, and many more. In Section 2, the author introduces the reader to the vast number of applications of computers in orthopedic surgery, with special emphasis on the emerging importance of virtual reality in all aspects of orthopedics, ranging from pre-operative planning, pre-operative surgical practice on virtual patients, and virtual wayfinding and navigation; through intra-operative virtual bone structure modeling to enhance accuracy; to, most importantly, post-operative or non-operative rehabilitation of orthopedic conditions using these new computer techniques. The book ends by stressing the importance of telerehabilitation, an increasingly important tool for ensuring that even patients living in remote rural areas can have the chance to participate in rehabilitation guided by a therapist through the use of a virtual environment and teleconferencing.